2021
DOI: 10.3390/molecules26051381
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid Restricts Human Bladder Cancer Cell Proliferation In Vitro by Inducing Caspase-Dependent Cell Death and Cell Cycle Arrest, and Decreasing Metastatic Potential

Abstract: Betulinic acid (BA) is a naturally occurring pentacyclic triterpenoid and generally found in the bark of birch trees (Betula sp.). Although several studies have been reported that BA has diverse biological activities, including anti-tumor effects, the underlying anti-cancer mechanism in bladder cancer cells is still lacking. Therefore, this study aims to investigate the anti-proliferative effect of BA in human bladder cancer cell lines T-24, UMUC-3, and 5637, and identify the underlying mechanism. Our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 78 publications
(94 reference statements)
0
13
0
Order By: Relevance
“…Betulinic acid decreases the levels of Snail, Slug and MMP-9 to inhibit the wound healing and invasion ability in bladder cancer cells. 86 Pristimerin, a triterpenoid isolated from celastrus and maytenus spp, reduces the expression of vimentin, MMP-2, F-actin, integrin β1, and Snail to suppress EMT-mediated H1299 cell migration and invasion, and it also suppresses cancer cell proliferation and drives cell apoptosis; 87 pristimerin inhibits the (Ephrin type-B receptor 4) EphB4/cdc42/N-WASP signals to promote ROS generation, cleavage of caspase-3/4/9, and expression of ER stress-associated proteins, thus consequently inducing mitochondrion-mediated intrinsic apoptosis and repressing cell viability, migration, and angiogenesis in conditionally reprogrammed patient-derived lung adenocarcinoma cells; 88 pristimerin could increase caspase-3/7 activity and reduce Bcl-2 expression to induce cell apoptosis. It also upregulates the expression of autophagy-associated proteins (p62 and LC3-II) as well as the unfolded protein response (UPR) to induce incomplete autophagy in breast cancer.…”
Section: Phytochemicals For Cancer Prevention and Therapymentioning
confidence: 99%
“…Betulinic acid decreases the levels of Snail, Slug and MMP-9 to inhibit the wound healing and invasion ability in bladder cancer cells. 86 Pristimerin, a triterpenoid isolated from celastrus and maytenus spp, reduces the expression of vimentin, MMP-2, F-actin, integrin β1, and Snail to suppress EMT-mediated H1299 cell migration and invasion, and it also suppresses cancer cell proliferation and drives cell apoptosis; 87 pristimerin inhibits the (Ephrin type-B receptor 4) EphB4/cdc42/N-WASP signals to promote ROS generation, cleavage of caspase-3/4/9, and expression of ER stress-associated proteins, thus consequently inducing mitochondrion-mediated intrinsic apoptosis and repressing cell viability, migration, and angiogenesis in conditionally reprogrammed patient-derived lung adenocarcinoma cells; 88 pristimerin could increase caspase-3/7 activity and reduce Bcl-2 expression to induce cell apoptosis. It also upregulates the expression of autophagy-associated proteins (p62 and LC3-II) as well as the unfolded protein response (UPR) to induce incomplete autophagy in breast cancer.…”
Section: Phytochemicals For Cancer Prevention and Therapymentioning
confidence: 99%
“…On the other hand, it has been reported that betulinic acid impairs the metastatic capability of cancer cells by inhibition of EMT. Studies showed that betulinic acid repressed EMT by decreasing SNAIL, SLUG, Vimentin, and N-cadherin expression and by increasing E-cadherin expression in pancreatic [38], colorectal [39] and bladder cancer [40] cells. With our ndings, the inhibitory effect of betulinic acid on SDC-2 and its relationship with renal cancer were determined for the rst time in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The cells blocked in the G2/M phase further underwent apoptosis, which was confirmed by characteristic modifications, such as the up-regulation of BAX, the activation of caspase-8, -9, -3 cascade, and an increase in cleaved PARP concentrations ( Figure 4 ). The decrease of Snail, Slug, and matrix metalloproteinase-9 (MMP-9), three factors involved in cell migration, was also observed, suggesting that BA could inhibit cell migration by a yet unexplored mechanism of action [ 43 ]. Contrary to these findings, Zhang et al found that apoptosis induction in EJ and T24 human bladder cell lines was abolished or attenuated when an antioxidant was used, thus suggesting that BA is able to induce apoptosis in a ROS-dependent manner.…”
Section: Betulinic Acidmentioning
confidence: 99%